Glucocorticoid sensitivity: pathology, mutations and clinical implications. Issue 3 (May 2006) - Ray, David W; Donn, Rachelle; Berry, Andrew
Glucocorticoids exert diverse effects on virtually all cell types and tissues. Subtle changes in sensitivity may be generalized and congenital or acquired in a tissue-specific manner. Such changes may lead to altered susceptibility to metabolic diseases, such as ischemic heart disease, or to insensitivity to the therapeutic actions of synthetic glucocorticoids such as in inflammatory disease. This review will cover current theories of how glucocorticoids exert genetic and other congenital effects on glucocorticoid sensitivity, and acquired changes in glucocorticoid sensitivity seen principally in inflammatory and malignant disease. Recent important developments in the field include the impact of genetic variation within the glucocorticoid receptor gene, the effects of early life experience on long-term glucocorticoid sensitivity, studies identifying the role of nuclear factor κκB in modulating glucocorticoid sensitivity in vitro and in vivo, and the action of macrophage migration inhibitory factor in modulating the anti-inflammatory effects of glucocorticoids. The role of chromatin organization in regulating glucocorticoid action on proinflammatory genes is discussed, as is the regulation of glucocorticoid sensitivity in human malignancy in the context of pathogenesis and treatment response.